New-Onset Refractory Status Epilepticus with Claustrum Damage: Definition of the Clinical and Neuroimaging Features - Meletti, Stefano; Giovannini, Giada; d’Orsi, Giuseppe; Toran, Lisa; Monti, Giulia; Guha, Rahul; Kiryttopoulos, Andreas; Pascarella, Maria Grazia; Martino, Tommaso; Alexopoulos, Haris; Spilioti, Martha; Slonkova, Jana (Frontiers in Neurology, 2017)
New-onset refractory status epilepticus (NORSE) is a rare but challenging condition occurring in a previously healthy patient, often with no identifiable cause. We describe the electro-clinical features and outcomes in a group of patients with NORSE who all demonstrated a typical MRI sign characterized by bilateral lesions of the claustrum. The group includes 31 patients (12 personal and 19 previously published cases; 17 females; mean age of 25 years). Fever preceded SE in twenty-eight patients, by a mean of six days. SE was refractory/super-refractory in 74% of the patients, requiring third line agents and a median of 15 days staying in an intensive care unit. Focal motor and tonic-clonic seizures were observed in 90%, complex partial seizures in 14%, and myoclonic seizures in 14% of the cases. All patients showed T2/FLAIR hyper-intense foci in bilateral claustrum, appearing on average 10 days after SE onset. Other limbic (hippocampus, insular) alterations were present in 53% of patients. Within the personal cases, extensive search for known auto-antibodies was inconclusive, though in 7 of 11 patients had CSF lymphocytic pleocytosis and three cases had oligoclonal bands. Two subjects died during the acute phase, one in the chronic phase (probable sudden unexplained death in epilepsy), and one developed a persistent vegetative state. Among survivors, 80% developed drug-resistant epilepsy. Febrile-illness related SE associated with bilateral claustrum hyperintensity on MRI represents a homogeneous condition with defined clinical features and a presumed but unidentified autoimmune aetiology. A better characterization of de novo SE is mandatory for the search of specific etiologies.